Immunomodulatory Effect of Adipose-Derived Stem Cells: The Cutting Edge of Clinical Application - Ceccarelli, Simona; Pontecorvi, Paola; Anastasiadou, Eleni; Napoli, Claudio; Marchese, Cinzia (Frontiers in Cell and Developmental Biology, 2020)
Adipose derived stem cells (ASCs) represent a promising tool for soft tissue engineering as well as for clinical treatment of inflammatory and autoimmune pathologies. The well-characterized multi-differentiation potential and self-renewal properties of ASCs are coupled with their immunomodulatory ability in providing therapeutic efficacy. Yet, their impact in immune or inflammatory disorders might rely both on cell contact-dependent mechanisms and paracrine effects, resulting in the release of various soluble factors that regulate immune cells functions. Despite the widespread use of ASCs in clinical trials addressing several pathologies, the pathophysiological mechanisms at the basis of their clinical use have been not yet fully investigated. In particular, a thorough analysis of ASC immunomodulatory potential is mandatory. Here we explore such molecular mechanisms involved in ASC immunomodulatory properties, emphasizing the relevance of the milieu composition. We review the potential clinical use of ASC secretome as a mediator for immunomodulation, with a focus on in vitro and in vivo environmental conditions affecting clinical outcome. We describe some potential strategies for optimization of ASCs immunomodulatory capacity in clinical settings, which act either on adult stem cells gene expression and local microenvironment. Finally, we discuss the limitations of both allogeneic and autologous ASC use, highlighting the issues to be fixed in order to significantly improve the efficacy of ASC-based cell therapy.